Protective Effect of Nigella Sativa on Isoniazid Induced Hepatic Toxicity in Rabbits - Panezai, Abdullah Jan (International Journal of Pathology, 2023)
Introduction: The potential of ATT treatment regimens to induce hepatotoxicity necessitates a suitable adjunct therapy to diminish such effects. Nigella sativa is a herbal product. It has also been used as an anti-spasmodic, anti-oxidant, anti-asthmatic, anti-inflammatory, analgesic and an immune modulatory agent. Objective: To evaluate the protective effect of Nigella sativa in Isoniazid (INH)-induced hepatic toxicity in rabbits Material and Methods: This Randomized case-control study was conducted in the Department of Pharmacology and Therapeutics, BMSI, Karachi, in collaboration with the Animal house of BMSI, JPMC Karachi. In the current animal study 48 (N) healthy rabbits of either sex were randomly selected and divided into four groups comprising of 12 (n) rabbits in each group. Group-I was given a healthy diet only, Group-II was given only Isoniazid (INH) 50mg/kg body weight per day orally, Group-III was given INH 50mg/kg plus Nigella sativa 500 mg/kg body weight per day orally and Group-IV was given INH 50mg/kg plus Nigella sativa 1g/kg body weight per day orally. The treatment duration lasted for 20 days. Tissue sections were stained with Hematoxylin & Eosin stains, and observed under a light microscope using scanner (04x), low (10x) and high power (40x). The data was analyzed with using SPSS version 16. Paired T-Test and Chi-square were applied. Results: Hepatic tissue was observed with a variable degree of histopathological changes induced by INH-associated hepatic toxicity. The changes were either prevented or mitigated by giving Nigella sativa in combination therapy. Conclusion: Nigella sativa showed protective effects in INH-induced hepatic tissue injuries in rabbits